Optimasi Jangkauan Pelayanan Menara Telekomunikasi Melalui Integrasi Sistem Informasi Geografis Dan Model Lokasi-Alokasi Di Kecamatan Sangir Batang Hari - Rizki Zakiah; Risky Ramadhan (JURNAL SAINS INFORMASI GEOGRAFI, 2025)
The uneven availability of telecommunications networks is a serious problem for the community in Sangir Batang Hari District, as it limits access in the field of information and communication. This research is intended to conduct an analytical assessment of the coverage of telecommunication towers and determine the optimal location for the construction of new towers to support equitable communication services in the region using location allocation methods and simulations with Atoll software. The main parameters analyzed include RSRP (Reference Signal Received Power) values, topography, land use, and population distribution. The validation of the modeling results was collected through measurements along the main road using the G-NetTrack Pro application, which obtained actual signal strength data from 2.815 samples. The modeling results using Atoll software show that coverage with excellent quality (-70 dBm) covers an area of approximately 22,125 m². Good quality (-80 dBm) covers an area of approximately 152,900 m². Normal quality (-90 dBm) covers an area of 14,406,321.92 m². Meanwhile, poor quality (-100 dBm) covers an area of approximately 378,163,410.4 m² and very poor quality (